State and Social Reproduction: Submission and inequality for women - Seijas Nieves, Eudel (Sociedade em Debate, 2023)
With the intention of critically looking at the articulation between the State and the capitalist order, we have carried out a narrative review of the literature to address the proposal of female empowerment promoted for them as a possible solution to the condition of inequality they live in contemporaneity. Through a reflective process through various readings, we managed to define this strategy as an instrument of submission that responds to the dynamics of productivity and consumption, which does not free women from social commitments such as motherhood, upbringing and care of the home, the domestic. Fetishizing the exploitation of women, in a stoic and romantic way, under the promise of emancipation.